Foreign Brains in the Top European Universities: Import of non-European PhDs into Europe - sagara, takashi (Advances in Social Sciences Research Journal, 2015)
Europe has a strong ambition to gather the world’s brightest brains into the region. In order to measure the state of the dominance of the foreign brains in Europe, the study examines the proportion of foreign Doctor of Philosophy (PhD) in the top European top universities in Economics. The results of the examination on the one hand show that the top European universities are most dominated by the ‘self-supplied’ PhDs, namely the PhDs granted and held by the same universities and the same countries. On the other hand, the results demonstrate that the top European universities are dominated by the top American PhDs, by excluding the ‘self-supplied’ PhDs. Based on the results, this study concludes that Europe nearly fails to achieve the ambition and should more actively try to hold the world’s best PhDs as the ‘self-supplied’ PhDs are dominant in the region.